2012
DOI: 10.1051/0004-6361/201117674
|View full text |Cite
|
Sign up to set email alerts
|

The long-period Galactic Cepheid RS Puppis

Abstract: Context. The southern long-period Cepheid RS Pup is surrounded by a large circumstellar dusty nebula reflecting the light from the central star. Due to the changing luminosity of the central source, light echoes propagate into the nebula. This remarkable phenomenon was the subject of Paper I. The origin and physical properties of the nebula are however uncertain: it may have been created through mass loss from the star itself, or it could be the remnant of a pre-existing interstellar cloud. Aims. Our goal is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…The long-period Cepheid RS Pup is a particularly interesting object due to its location in a large reflection nebula (Westerlund 1961;Kervella et al 2008Kervella et al , 2012Feast 2008) and erratic period changes (Berdnikov et al 2009) that are also clearly seen in the present data. As the Coralie data shows, using non-contemporaneously determined ΔR and ΔΘ can lead to systematic errors of up to 7% for its BW distance.…”
Section: Rs Puppissupporting
confidence: 70%
“…The long-period Cepheid RS Pup is a particularly interesting object due to its location in a large reflection nebula (Westerlund 1961;Kervella et al 2008Kervella et al , 2012Feast 2008) and erratic period changes (Berdnikov et al 2009) that are also clearly seen in the present data. As the Coralie data shows, using non-contemporaneously determined ΔR and ΔΘ can lead to systematic errors of up to 7% for its BW distance.…”
Section: Rs Puppissupporting
confidence: 70%
“…This wavelength range is an optimal choice in terms of scattered light intensity, because the high flux from the yellow supergiant combines with the efficient scattering from the dust. Since the field-of-view (FoV) of the ACS/WFC polarizers (an unvignetted circular FoV with diameter 70 ) is smaller than the ∼3 size of the RS Pup nebula, we positioned the Cepheid near the edge of the FoV, and we focused on a bright, high polarization area of the nebula that was identified by Kervella et al (2012). Seven epochs of polarimetric imaging, equally spaced throughout a single pulsation cycle of RS Pup, were obtained between 2010 March 25 and April 29.…”
Section: Instrumental Setup and Raw Data Reductionmentioning
confidence: 99%
“…Although our current spatial resolution is comparatively coarse, we are able to place a 3σ upper limit on the mass of neutral atomic hydrogen within a radius of 38,000 AU from the star (i.e., one synthesized beam) of < M 0.11 HI ( Table 5). Looking to larger scales, Kervella et al (2012) found a mean radius of the RSPup reflection nebula to be ¢ 1.8 (∼0.8 pc for our adopted distance) based on the analysis of scattered light images, and they estimated the total quantity of gas plus dust within this volume to be…”
Section: Rs Pupmentioning
confidence: 95%
“…However, we find no statistically significant emission near the position of RSPup either in our H I channel maps (not shown) or in our integrated spectra. Over the total angular extent of the reflection nebula (~¢ 4 ; Kervella et al 2012), spatial filtering of emission by VLA should not be a factor (see Section 3). We conclude that any atomic hydrogen associated with mass loss from RSPup or with the RSPup reflection nebula is either below our detection threshold or lies at velocities affected by confusion from line-of-sight emission.…”
Section: Rs Puppis (Rs Pup)mentioning
confidence: 99%
See 1 more Smart Citation